1997
DOI: 10.1128/jb.179.20.6495-6498.1997
|View full text |Cite
|
Sign up to set email alerts
|

HrpA, a new ribosome-associated protein which appears in heat-stressed Mycobacterium bovis bacillus Calmette-Guérin

Abstract: A novel 18-kDa heat shock protein, HrpA, has been identified from Mycobacterium bovis BCG. HrpA was rapidly synthesized in membrane and ribosome fractions but not in the cytoplasmic fraction under heat shock stress. HrpA bound tightly to 70S ribosomes, mainly in 30S subunits. HrpA might be involved in the initiation step of translation at high temperature.Bacillus Calmette-Guérin (BCG), an attenuated strain of Mycobacterium bovis, is the most widely used live vaccine against tuberculosis in the world, but the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Although these experiments were performed using mouse models, they suggested that humoral immunity could at least modify or reduce the growth of Mtb [ 31 , 32 ]. HrpA was identified by Ohara et al in 1997 [ 60 ] with a 30% homology to Acr, which increases to 40% when comparing Acr core residues [ 61 ]. It was later demonstrated that the expression of HrpA is upregulated by heat-shock, nitrate, or macrophage engulfment, suggesting that HrpA is one of the early immune targets of Mtb antigens [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these experiments were performed using mouse models, they suggested that humoral immunity could at least modify or reduce the growth of Mtb [ 31 , 32 ]. HrpA was identified by Ohara et al in 1997 [ 60 ] with a 30% homology to Acr, which increases to 40% when comparing Acr core residues [ 61 ]. It was later demonstrated that the expression of HrpA is upregulated by heat-shock, nitrate, or macrophage engulfment, suggesting that HrpA is one of the early immune targets of Mtb antigens [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…4A). Second, each subcellular fraction from BCG was prepared as described previously (20). These samples were electron-transferred on the membrane and reacted with the and-MDPI antibody (Fig.…”
Section: Localization Of Mdpi In the Cellmentioning
confidence: 99%
“…It is conceivable that there are heterogeneous populations of tubercle bacilli during dormancy and actively multiplying phases within granulomatous lesions at the pre‐recurrence stage. In this study, we assessed antibody responses to 23 kinds of major M. tuberculosis proteins, including those expressed by growing and dormant bacilli obtained from individuals with past TB who were not currently receiving TB chemotherapy. The aim of this study was to explore biomarker‐targeted antibody responses in those who are at risk of TB progression.…”
mentioning
confidence: 99%